Implementasi Kebijakan Pemerintah Daerah Kabupaten Bekasi Dalam Pengentasan Kemiskinan Masyarakat - Putri Suciana; Usep Dayat; Gun Gun Gumilar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze and determine the implementation of local government policies in Bekasi Regency in alleviating community poverty (descriptive study in Cipayung Village, East Cikarang District). This research is a descriptive qualitative type with data collection techniques carried out using triangulation which includes interviews, observations and documentation studies, then the data is analyzed by reducing, presenting and drawing conclusions. The theory used is Edwards III's Policy Implementation in Putra (2001:9) in which there are four dimensions, namely nature, organizational structure, communication and resources. The results of this study indicate that the policies made by the Bekasi Regency Government have not gone well because the communication between the Regional Government Apparatus and the Cipayung Village Government has not been coordinated and has not been implemented and has not been implemented by the regional government in implementing poverty alleviation policies against the Bekasi Regency Regional Regulations. Number 10 of 2012 concerning the organizational structure has not yet created characteristics that are able to encourage Small and Medium Micro Business actors to develop better.